Factors influencing voluntary disclosure: empirical evidence from shariah approved companies / A. A. Ousama and A. H. Fatima - Ousama, Abdulrahman Anam; Abdul Hamid, Fatima (Universiti Teknologi MARA Cawangan Selangor, 2010)
The objective of the current study is to examine the relationship between the extent of voluntary disclosure (i.e. overall, conventional and Islamic disclosure items) and firm-specific characteristics (i.e. size, ownership structure, audit firm and industry) of Shariah Approved Companies (ShAC). The study used a disclosure index, consisting of 59 items, to measure the extent of voluntary disclosure. The data were collected from the 2003 annual eports of the top 50 ShAC. The main statistical tests conducted were: descriptive statistics, correlation and regression. Generally, the results show that firm size is statistically associated with the extent of voluntary disclosure in all three categories. While, the ownership structure is significant with overall and conventional voluntary disclosure, the type of audit firm is significant with the overall and Islamic voluntary disclosure. Moreover, regression results indicate that non-manufacturing ShAC seem to voluntarily disclose more Islamic items than manufacturing companies.